Records of sedimentary dynamics in the continental shelf and upper slope between Aveiro-Espinho (N Portugal) - Martins, V. (2012)
The sedimentary unconsolidated cover of the Aveiro–Espinho continental shelf and upper slope (NW Portugal) records a complex interplay of processes including wave energy and currents, fluvial input, sediment transport alongshore and cross-shelf, geological and oceanographic processes and sediment sources and sinks. In order to study this record, a set of surface sediment samples was studied. Sediment grain size and composition, as well as the mineralogical composition (by XRD) of the fine (< 63 μm) and clay (< 2 μm) fractions and benthic microfaunal (foraminifera) data were analysed. Cluster analysis applied to the sedimentological data (grain size, sediment composition and mineralogy) allowed the establishment of three main zones corresponding to the: inner-, mid- and outer-shelf/upper slope. On the inner-shelf, the sedimentary coverture is composed of siliciclastic fine to very fine sand, essentially comprising modern (immature) terrigenous particles. The sediment grain size, as well as mineralogical and microfaunal composition, denote the high energetic conditions of this sector in which the alongshore transport of sand is predominantly southward and occurs mostly during the spring–summer oceanographic regime, when the main river providing sediments to this area, the River Douro, undergoes periods of drought. This effect may emphasize the erosive character of this coastal sector at present, since the Ria de Aveiro provides the shelf with few sediments. On the mid-shelf, an alongshore siliciclastic band of coarse sand and gravel can be found between the 40 m and 60 m isobaths. This gravelly deposit includes relic sediments deposited during lower sea-level stands. This structure stays on the surface due to the high bottom energy, which promotes the remobilization of the fine-grained sediments, and/or events of sediments bypassing. Benthic foraminifera density and “Benthic Foraminifera High Productivity” (BFHP) proxy values are in general low, which is consistent with the overall small supply of organic matter to the oceanic bottom in the inner- and mid-shelf. However, the Ria de Aveiro outflow, which delivers organic matter to the shelf, leaves its imprint mainly on the mid-shelf, identifiable by the increase in foraminifera density and BFHP values in front of the lagoon mouth. The higher values of BFHP along the 100 m isobath trace the present position of an oceanic thermal front whose situation may have changed in the last 3/5 ka BP. This zone marks a clear difference in the density, diversity and composition of benthic foraminifera assemblages. Here, in addition, sediment composition changes significantly, giving rise to carbonate-rich fine to medium sand in the deeper sector. The low bottom energy and the small sedimentation rate of the outer-shelf contributed to the preservation of a discontinuous carbonate-rich gravel band, between the 100 m and 140 m isobaths, also related to paleo-littorals, following the transgression that has occurred since the Last Glacial Maximum. The winter oceanographic regime favours the transport of fine grained sediments to the outer-shelf and upper slope. The inner- and mid-shelf, however, have low amounts of this kind of sediment and the Cretacic carbonated complexes Pontal da Galega and Pontal da Cartola, rocky outcrops located at the mid- and outer-shelf, act as morphological barriers to the cross-shelf transport of sediments. Thus a reduced sedimentation rate occurs in these deeper sectors, as indicated by the lower abundance of detrital minerals, which is compensated for the high sedimentary content of biogenic carbonates. The relatively high BFHP and Shannon Index values indicate water column stratification, high supply of organic matter and environmental stability, which provide favourable conditions for a diversified benthic fauna to flourish. These conditions also encourage authigenic chemical changes, favourable to glauconite formation, as well as illite and kaolinite degradation. Benthic foraminifera and clay mineral assemblages also reveal the effect of the internal waves pushing upward, and downslope losses of the sediments on the outer-shelf and upper slope.